2020
DOI: 10.5194/se-11-2015-2020
|View full text |Cite
|
Sign up to set email alerts
|

Using horizontal-to-vertical spectral ratios to construct shear-wave velocity profiles

Abstract: Abstract. For seismic hazard assessment and earthquake hypocentre localization, detailed shear-wave velocity profiles are an important input parameter. Here, we present a method to construct a shear-wave velocity profiles for a deep unconsolidated sedimentary layer by using strong teleseismic phases and the ambient noise field. Gas extraction in the Groningen field, in the northern part of the Netherlands, is causing low-magnitude, induced seismic events. This region forms an excellent case study due to the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 56 publications
(74 reference statements)
2
20
0
Order By: Relevance
“…Local earthquake recordings in boreholes over a range of depth levels show that the largest amplification occurs in the top 50 meters of the sedimentary cover, although the entire sediment layer has a thickness of around 800 m in this region. Furthermore, van Ginkel et al (2019) showed existence of a the correlation between the spatial distribution of microtremor horizontal-to vertical spectral ratio (HVSR) peak amplitudes and the measured earthquake amplification. This observation is in accordance with e.g.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Local earthquake recordings in boreholes over a range of depth levels show that the largest amplification occurs in the top 50 meters of the sedimentary cover, although the entire sediment layer has a thickness of around 800 m in this region. Furthermore, van Ginkel et al (2019) showed existence of a the correlation between the spatial distribution of microtremor horizontal-to vertical spectral ratio (HVSR) peak amplitudes and the measured earthquake amplification. This observation is in accordance with e.g.…”
Section: Introductionmentioning
confidence: 95%
“…Various studies (van Ginkel et al, 2019;Kruiver et al, 2017a, b;Bommer et al, 2017;Noorlandt et al, 2018) undertaken in the Groningen area concluded that unconsolidated sediments were responsible for significant amplification of seismic waves over a range of frequencies pertinent to engineering interest. Although the local earthquake magnitudes are relatively small, the damage on the houses can be significant.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations